Загальні принципи і структура нормативно-технічного забезпечення у сфері систем енергетики - Stoyanova I.I.; Sokolovska I.S. (General Energy Institute of the National Academy of Sciences of Ukraine, 2001)
The general principles and the structure of standards for a fuel and energy complex on the base of new approach according to the International Standards ISO of the 13600 series are suggested. The general characteristic of this approach with introduction of new terms "technical energy systems" and "energyware" is given, and the main kinds of activity for each sector of energyware production and energyware consumption are described.